PERANAN PSAK NO 33 PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Widagdya, Fiqhan Prananta (Jurnal Akuntansi AKUNESA, 2014)
Accounting is an information system which produces the report to the parties concerned about the economic activities and condition of the company. Economic information generated is expected to be useful in the assessment and decision-making about the business entity concerned. Mining business is an activity to optimize the use natural resources mining (minerals) found in the Earth Indonesia. Keywords : Accounting, Mining business